Photo-enhanced catalytic hydrogen production from ammonia borane dehydrogenation over cobalt doped n-type semiconductors - Filiz, Bilge Coskuner; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Aimed at achieving the photo-enhanced dehydrogenation of ammonia borane (NH3BH3) in aqueous solutions, p-type cobalt (Co) doped n-type semiconductors (TiO2, WO3 and TiO2WO3) based heterojunction structures were proposed for hydrogen production. In the present study, the Co doped n-type semiconductors such as titanium dioxide (TiO2) and tungsten oxide (WO3) were synthesized by hydrothermal synthesis to obtain heterojunction structure and characterized by XRD, SEM/EDS, TEM, FT-IR and UV-Vis techniques. The photo-enhanced catalytic hydrogen production from NH3BH3 dehydrogenation over Co doped n-type semiconductors were tested under light-irradiation (UV-light and day-light) in presence of organic and inorganic scavengers. The experimental results showed that Co @TiO2-WO3 heterojunction structure improved hydrogen production almost three times in terms of TOF values (821 h-1) compared to Co@TiO2 (292 h-1) due to photoelectrons and hole pairs increases activity. The pseudo first order kinetics based on LangmuirHinshelwood (L-H) kinetic model fitting revealed that apparent adsorption constant
Keywords: UV-Vis; Photo-catalytic; TiO 2; Hydrogen; Heterojunction; WO3; PHOTOCATALYTIC HYDROLYSIS; EFFICIENT CATALYSTS; H-2 EVOLUTION; NANOPARTICLES; NANOFIBERS; NANOWIRES; NANORODS; ANATASE; Chemistry; Electrochemistry; Energy & Fuels